Metabolit dan Profil Darah Ayam Akhir Periode Bertelur yang Disuplementasi Enzim Bromelin dalam Ransumnya: Metabolite and Blood Profile of Late Laying Period Supplemented with Bromelain Enzyme in The Ration - Rafis, Herlan; Sudarman, A; Mutia, Rita (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This experiment aimed to evaluate the effect of bromelain enzyme supplementation in a late-laying period diet on blood metabolite and blood profile parameters. A total of 200 Isa Brown at late laying period hens, 85 weeks of age, were randomly distributed into four dietary treatments and fed for eight weeks. The bromelain enzyme was used at the level of 0% (control diet), 0.025%, 0.050%, and 0.075%. Each treatment was replicated five times. Experimental design data were analyzed using ANOVA and Duncan multiple range test. Bromelain supplementation had a significant effect on the concentration of blood protein (p<0.01), reduced blood cholesterol (p<0.05), and increased concentration of immunoglobulin Y (IgY) (p<0.05). It is concluded that supplementation at dosages 0.05% and 0.075% of bromelain can improve the birds' immunity by increasing the IgY content in blood serum. supplementation at 0.05% reduces blood cholesterol and increases blood protein. Key words: blood metabolite, blood profile, bromelain, IgY, late laying period